Hey! Great to see you again.
Based on what we learned last time, we can apply it to this equation!
Solve 3x+y =−5 for y:
3x+y=−5
3x+y+−3x=−5+−3x Let us add -3x to both sides.
y=−3x−5.
Substitute −3x−5 for y in −2x+3y=18:
−2x+3y=18
−2x+3(−3x−5)=18
−11x−15=18 Simplify both sides :)
−11x−15+15=18+15 Add 15 to each side.
−11x=33
x = -3
Now solve for y.
−3 for x in y=−3x−5:
y=(−3)(−3)−5
Can you solve this equation? Let me know if you need help, tell me what you get! :) That will be your y answer. :D
Have a great one!